Silver oxide nanoparticles in reduced graphene oxide modified electrode for amino acids electrocatalytic oxidation - Azevedo, Victor Hugo Romeiro [UNESP]; da Silva, José Luiz [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Elsevier, 2019)
A glassy carbon electrode (GCE) modified with reduced graphene oxide (RGO) and silver oxide nanoparticles (AgNPs-RGO/GCE) was prepared for electrocatalytic oxidation of amino acids. The modified electrode surface was characterized by scanning electron microscopy, energy dispersive X-ray spectroscopy, X-ray photoelectron spectroscopy and Raman spectroscopy. The results showed that the developed AgNPs had a medium diameter of 10 ± 2 nm besides being well dispersed on the RGO surface. The electrochemical behavior of the AgNPs-RGO/GCE in the oxidation of glycine, alanine, leucine, aspartic and glutamic acids was carried out by cyclic voltammetry and amperometric techniques. Voltammetric studies indicated a rise in the anodic peak of the silver (III) oxide species in the presence of amino acids. Essentially, this shows that amino acids were oxidized in the redox mediator was electrodeposited on the electrode surface via an electrocatalytic process. Based on Laviron's equation, the values of α and ks for the redox species were found to be 0.51 and 0.61 s−1, respectively. The catalytic rate constants of 1.4 × 108 (alanine) to 5.4 × 108 cm3 mol−1 s−1 (glycine), the transfer coefficients 0.37 (leucine) to 0.45 (glutamic acid), and the diffusion coefficients of 1.1 × 10−6 (alanine) to 7.7 × 10−6 cm2 s−1 (glycine) for the amino acids are reported. The excellent electrocatalytic activity, high sensitivity and good stability observed in our investigation renders the AgNPs-RGO/GCE promising for application as a suitable sensor for amino acids detection.
Keywords: Amino acids; Electrochemical oxidation; Modified electrode; Reduced graphene oxide; Silver oxide nanoparticle